Evaluation of N-acetilglucosaminidase and myeloperoxidase activity in patients with endometriosis-related infertility undergoing intracytoplasmic sperm injection - Lamaita, Rivia Mara [UNESP]; Pontes, Anaglória [UNESP]; Belo, Andrezza V.; Caetano, Joao Pedro; Andrade, Silvia P.; Candido, Eduardo B.; Carneiro, Marcia Mendonca; Silva-Filho, Agnaldo L. [UNESP] (Wiley-Blackwell, 2012)
Aim: Inflammation is as an important factor in ovulation with the active participation of leucocytes and their inflammatory mediators. The present study was performed to compare the activity of the inflammatory enzymes myeloperoxidase (MPO) and N-acetylglucosaminidase (NAG) in patients with endometriosis-related infertility and in normally ovulating women undergoing intracytoplasmic sperm injection (ICSI).Material and Methods: This prospective study included infertile women undergoing ICSI treatment. These women were divided into two groups: endometriosis anovulation (n = 18) and normally ovulating (n = 20). NAG and MPO activity was evaluated colorimetrically in serum and in follicular fluids obtained at the time of oocyte retrieval.Results: There was a significant correlation between the serum and follicular fluid activities of NAG and MPO (tau = 0.256, P = 0.025; and tau = -0.234, P = 0.041; respectively). Both serum and follicular fluid NAG activities were higher in patients with endometriosis compared to the control group (P < 0.001). MPO follicular fluid activity was lower in patients with endometriosis compared to normally ovulating women (P = 0.016).Conclusion: Infertile patients with endometriosis show a distinct pattern of serum and follicular fluid macrophage/neutrophil activation compared to normally ovulating women undergoing ICSI, which may reflect the role of immune and inflammatory alterations in endometriosis-related infertility.
Keywords: endometriosis; infertility; inflammation; myeloperoxidase; N-acetylglucosaminidase